Learning Node.js for .NET developers : solve practical real-world problems using JavaScript and Node.js - Cummings, Harry (Community experience distilled., 2016)
Solve practical real-world problems using JavaScript and Node.js About This Book Learn the concepts of Node.js to gain a high-level understanding of the Node.js execution model Build an interactive web application with MongoDB and Redis and create your own JavaScript modules that work both on the client side and server side Familiarize yourself with the new features of Node.js and JavaScript with this exclusive step-by-step guide Who This Book Is For This book is for developers who want to learn JavaScript and Node.js. Previous experience with programming is desired, but no JavaScript or Node.js knowledge is required. The book focuses mostly on web development, such as networking, serving dynamic pages, and real-time client-server communication. What You Will Learn Understand which problems Node.js best solves Write idiomatic JavaScript and Node.js code Build web applications and command-line tools Minimise complexity and efficiently solve difficult problems Test and deploy Node.js applications Work with persistent data Implement real-time client-server applications Integrate .NET and Node.js code In Detail Node.js is an open source, cross-platform runtime environment that allows you to use JavaScript to develop server-side web applications. This short guide will help you develop applications using JavaScript and Node.js, leverage your existing programming skills from .NET or Java, and make the most of these other platforms through understanding the Node.js programming model. You will learn how to build web applications and APIs in Node, discover packages in the Node.js ecosystem, test and deploy your Node.js code, and more. Finally, you will discover how to integrate Node.js and .NET code. Style and approach This is a step-by-step and practical guide to Node.js for .Net developers. It covers the fundamentals relating to typical applications. The focus is on providing the practical skills required to develop applications, with a summary of the key concepts covered.